Assessing the impact of ChatGPT on enhancing learning in preclinical and clinical dental education - Tayyaba Nayab; Malik Adeel Anwar; Ammara Chaudhry; Annam Imtiaz; Gulrez Amin; Nimra Meraj (Journal of University Medical & Dental College, 2025)
BACKGROUND & OBJECTIVE: Artificial intelligence (AI) is transforming not only education but also healthcare. ChatGPT, offers new opportunities for interactive learning. This study assessed its benefits, challenges, and applications in pre-clinical and clinical dental education.METHODOLOGY: A cross-sectional, questionnaire-based survey was conducted among 300 undergraduate dental students (preclinical and clinical) in Lahore. A validated self-administered questionnaire assessed knowledge, perceptions, and practices. Data were analyzed using SPSS v25.0; chi-square test was applied with significance set at p ≤ 0.05.RESULTS: Awareness of ChatGPT was high (96%). Active use as a learning tool was reported by 86%, with higher use among clinical students (95%) compared to preclinical students (76%) (p<0.001). While 94% expressed interest in integrating ChatGPT into future education, challenges included lack of formal training (49%), difficulties in usage (97%), and skepticism about its relevance to clinical dentistry (46%). Although 89% recognized its role in providing current literature, 72% reported unreliable or inadequate information regarding clinical dentistry.CONCLUSION: ChatGPT is widely adopted as a learning adjunct among dental students, particularly in clinical years. Despite its potential to enhance communication and evidence-based learning, concerns regarding accuracy, reliability, and ethical integration remain. Careful incorporation into curricula is necessary to maximize benefits while addressing limitations.